The Ngobeng Tradition in Palembang: Implementing Local Wisdom and Religious Moderation in Multicultural Education to Achieve Social Harmony - Rohmadi; Achmad Fadil; Zaki Faddad Syarif Zain; Nyayu Soraya (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
Ngobeng tradition in Palembang is a community practice of serving food at religious and social events. This tradition has received increasing academic attention due to its role in building inter-group relations amidst increasing social and religious polarization in a multicultural society. In the context of multicultural education, Ngobeng is a learning tool that instills the values of togetherness, tolerance and respect for diversity in social life. The purpose of this study is to examine the contribution of Ngobeng tradition to multicultural education by combining local wisdom and religious moderation values to create social harmony. This research uses a qualitative method with an ethnographic approach, through participatory observation in the implementation of the Ngobeng tradition, in-depth interviews with community leaders and residents, and literature review of relevant cultural and educational theories. The results showed a dynamic integration between cultural practices and religious values. The Ngobeng tradition not only strengthens relationships between individuals across social and religious groups, but also serves as a medium for multicultural learning. Abstrak Tradisi Ngobeng di Palembang merupakan praktik masyarakat dalam menyajikan makanan pada acara keagamaan dan sosial. Tradisi ini semakin mendapat perhatian akademik karena perannya dalam membangun hubungan antar kelompok di tengah meningkatnya polarisasi sosial dan keagamaan di masyarakat multikultural. Dalam konteks pendidikan multikultural, Ngobeng menjadi sarana pembelajaran yang menanamkan nilai kebersamaan, toleransi, dan penghargaan terhadap keberagaman dalam kehidupan sosial. Tujuan penelitian ini mengkaji kontribusi tradisi Ngobeng terhadap pendidikan multikultural dengan menggabungkan kearifan lokal dan nilai moderasi beragama untuk menciptakan harmoni sosial. Penelitian ini menggunakan metode kualitatif dengan pendekatan etnografi, melalui observasi partisipatif dalam pelaksanaan tradisi Ngobeng, wawancara mendalam dengan tokoh masyarakat dan warga, serta telaah pustaka terhadap teori-teori budaya dan pendidikan yang relevan. Hasil penelitian menunjukkan adanya integrasi yang dinamis antara praktik budaya dan nilai-nilai keagamaan. Tradisi Ngobeng tidak hanya mempererat hubungan antarindividu lintas kelompok sosial dan agama, tetapi juga menjadi media pembelajaran multikultu Keywords: Ngobeng Tradition; Local Wisdom; Religious Moderation; Multicultural Education